A Process × Domain Assessment of Narcissism: The Domain-Specific Narcissistic Admiration and Rivalry Questionnaire. (October 2022) - Grosz, Michael P.; Hartmann, Isabel; Dufner, Michael; Leckelt, Marius; Gerlach, Tanja M.; Rauthmann, John F.; Denissen, Jaap J. A.; Küfner, Albrecht C. P.; Back, Mitja D.
Research on grandiose narcissism distinguishes between self-promotional processes (i.e., narcissistic admiration ) and other-derogative processes (i.e., narcissistic rivalry ; Back et al., 2013). Moreover, research has begun to assess and investigate narcissistic manifestations in different domains (e.g., communal narcissism). To integrate these two lines of research, we developed the Domain-Specific Narcissistic Admiration and Rivalry Questionnaire (D-NARQ), a 72-item narcissism questionnaire that contains a self-promotional process scale (narcissistic admiration) and an other-derogatory process scale (narcissistic rivalry) for four domains: intellectual ability, social dominance, communal care, and physical attractiveness. We investigated the psychometric properties of the D-NARQ in a large online study ( N = 1, 635). Model fit statistics were largely in line with the theorized factor structure. The D-NARQ scales had good to very good measurement precision, and their correlations with established narcissism scales, the Big Five personality traits, and comparative self-evaluations largely supported their convergent and discriminant validity.